Analysis of Protein‐Protein Interactions by Split Luciferase Complementation Assay. Issue 1 (2nd December 2019) - Lang, Yuekun; Li, Zhong; Li, Hongmin
Abstract: Protein‐protein interactions are important in human disease. Developing and refining tools to understand physical contacts between signaling proteins is crucial. This article describes a split luciferase complementation (SLC) method designed to discover inhibitors of protein‐protein interaction. Different fusion proteins with split luciferase are constructed, expressed, and purified, and then assessed to determine the best pair that generates the strongest luminescence. SLC specificity and affinity are further confirmed. Step‐by‐step instructions are provided for performing these assays using the NS2B‐NS3 interaction as an example. NS2B is an essential cofactor for flaviviral NS3 protease function. Advantages and disadvantages of these assays are further discussed. © 2019 by John Wiley & Sons, Inc. Basic Protocol 1 : Expression and purification of fusion proteins Basic Protocol 2 : Analysis of prey/bait pairs by SLC‐based NS2B‐NS3 interaction assay Support Protocol 1 : Interaction specificity assay Support Protocol 2 : Competition binding assay: Dose‐response inhibition using cold prey or bait Support Protocol 3 : Competition binding assay: Inhibition by MBP‐NS3 versus irrelevant MBP tag Support Protocol 4 : SLC‐based NS2B‐NS3 interaction assay using NS2B mutations known to disrupt NS2B‐NS3 interactions